Organic food preservatives / Baizatul Umi Umairah Mat Shufi, Siti Aisyah Md Ruzi and Nur Falah Aqilah Ah Bakri - Mat Shufi, Baizatul Umi Umairah; Md Ruzi, Siti Aisyah; Ah Bakri, Nur Falah Aqilah (Faculty of Plantation and Agrotechnology, 2023)
Chemical-based preservatives are often used by farm workers, farmers and suppliers of fruits and vegetables to ensure that both fruits and vegetables last longer and do not spoil during the storage period. But the use of chemical based materials has a negative impact on the health of users in the long term. So, this experiment aims to study the effectiveness of organic preservatives that based on herb source which is cloves. This experiment was tested on both of apples and bananas and on 18th December 2023. We decided to used two apples where are one apple labelled as “with spray” and another one apple labelled as “without spray”. We do the same thing to bananas fruit. We made an observation on several aspects and started with aspects of physical appearance (%), taste, fruit structure, spoilage period and smell then made a comparison between fruit with spray and fruit without spray. The equipment used is spoon, bowl, pot and stove. The materials used are twenty pieces of cloves, two cups of water, one teaspoon of salt, five pieces of kaffir lime leaves, bottle spray, seal plastic and sticker. The result of observation shows that fruits that sprayed by an organic preservatives was last longer than fruit without sprayed by an organic preservatives.